2013
DOI: 10.3390/molecules18044308
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition, Antifungal and Insecticidal Activities of Hedychium Essential Oils

Abstract: The antimicrobial properties of essential oils have been documented, and their use as “biocides” is gaining popularity. The aims of this study were to analyze the chemical composition and assess the biological activities of Hedychium essential oils. Oils from 19 Hedychium species and cultivars were analyzed by gas chromatography (GC) and gas chromatography-mass spectrometry (GC-MS) techniques. The antifungal and insecticidal activities of these oils were tested against Colletotrichum acutatum, C. fragariae, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 47 publications
1
50
0
1
Order By: Relevance
“…Monoterpene constituents detected in the present study such as 4-thujanol, fenchol, p-menth-2-en-1-ol, camphor, pinocarvone and bornyl acetate were absent in the earlier reports [18] . At the same time the monoterpenes detected in the essential oil of H. forrestii like, sabinene, myrcene, limonene, cymene, translinalool oxide and cis-linalool oxide were not found in the present study.…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…Monoterpene constituents detected in the present study such as 4-thujanol, fenchol, p-menth-2-en-1-ol, camphor, pinocarvone and bornyl acetate were absent in the earlier reports [18] . At the same time the monoterpenes detected in the essential oil of H. forrestii like, sabinene, myrcene, limonene, cymene, translinalool oxide and cis-linalool oxide were not found in the present study.…”
Section: Resultsmentioning
confidence: 63%
“…It is interesting to see that, though the oils of both taxa contained monoterpenes (87.5% in H. forrestii) and sesquiterpenes (8.33% in H. forrestii), hydrocarbon sesquiterpenes were not detected in H. forrestii. However, a diterpene was found in the rhizome essential oil of H. forrestii [18] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that rhizome oil of H. thyrsiforme, H. flavum and H. bousigonianum were dominated by 1,8 cineole, whereas linalool was the major constituent in H. forrestii and H. coccineum. -Pinene was also found to be the major rhizome oil component in H. elatum and H. flavescens (Sakhanokho et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Hedychium species are a good source of various essential oil compounds having medicinal and other industrial applications (Sakhanokho et al, 2013). The essential oil obtained from leaves of H. coronarium constituted -pinene as the major compound (Raj et al, 2013), whereas -ocimene and linalool as the major constituents in its flower oil (Báez et al, 2011) and 1,8 cineole as the major compound in rhizome oil (Joy et al, 2007).…”
Section: Introductionmentioning
confidence: 99%